Westminster Abbey
So advanced was the work at Gloucester that it is interesting to compare it with the nave of Westminster, which slowly pursued the course of its earlier rebuilding. Hardly completed by the time of the Reformation, it nevertheless employed almost all of the masons who had survived the years of plague. The vault of the nave stands 102 feet high- the highest Gothic vault in England- supported by a complex system of flying buttresses. The triforium stage, which was retained at Westminster for in use in coronation ceremonials.